Developing Android-Based Applications To Improve Reading Skills | تطوير التطبيقات المستندة الأندروئيدية لتحسين مهارة القراءة - Riyadus Sholihin, Nur; Hasanah, Luthfi (ATHLA : Journal of Arabic Teaching, Linguistic and Literature, 2023)
The use of learning applications represents an innovative development in educational media aimed at enhancing the quality of learning. The development of learning applications for Class VII at MTsN 1 Karanganyar is driven by the limited availability of technology-based teaching materials and a lack of proficiency in Arabic reading skills among students. This study aims to create an Android-based learning application and assess its impact on improving reading abilities among Class VII students at MTsN 1 Karanganyar. This research follows the ADDI method, comprising four stages: needs analysis, design, development, and implementation. Data collection techniques included observation, interviews, tests, questionnaires, and expert validation. The study's results indicate a significant improvement in learning achievement when using an Android-based learning application, with no students scoring below the class's minimum passing grade. The feasibility test results for the learning application showed approval from various experts: material experts at 78% (good), design experts at 75% (good), Arabic language studies teachers at 93% (very good), and student responses at 91% (very good).